Application of an automated aircraft architecture generation and analysis tool to unmanned aerial vehicle subsystem design - Judt, David M.; Lawson, Craig P. (SAGE Publications, 2014)
The work presents the application of a new computational framework, addressing future preliminary design needs for aircraft subsystems. The ability to investigate multiple candidate technologies forming subsystem architectures is enabled with the provision of automated architecture generation, analysis and optimisation. The core aspects involve a functional decomposition, coupled with a synergistic mission performance analysis on the aircraft, architecture and component level. This may be followed by a complete enumeration of architectures combined with a user-defined technology filtering and concept ranking procedure. In addition, a novel hybrid heuristic optimiser, based on ant colony optimisation and a genetic algorithm, is employed to produce optimal architectures in both component composition and design parameters. The framework is applied to the design of a regenerative energy system for a long endurance high altitude unmanned aerial vehicle, considering various emerging technologies. A comparison with the traditional design processes and certification requirements is made as well as technology trends summarised and substantiated.
Keywords: Subsystem design; multi-disciplinary analysis; heuristic optimisation